2015
DOI: 10.1099/mic.0.000045
|View full text |Cite
|
Sign up to set email alerts
|

EF0176 and EF0177 from Enterococcus faecalis V583 are substrate-binding lipoproteins involved in ABC transporter mediated ribonucleoside uptake

Abstract: One of the ABC transporter systems in Enterococcus faecalis V583 is encoded by the ef0176-ef0180 gene cluster, which differs from orthologous operons in related bacteria in that it contains two genes putatively encoding substrate-binding proteins (SBPs). These SBPs, EF0176 and EF0177, have previously been identified on the surface of E. faecalis. By phenotypic studies of single and double knockout mutants, we show here that EF0176 and EF0177 are specific for ribonucleosides and, by inference, that the EF0176-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Phylogenetic and homology analyses indicated that the efflux protein encoded by OG1RF_RS00630 is an ATPbinding cassette family protein expressed mainly in the cellular membrane. A previous study showed that the ortholog of OG1RF_RS00630 (EF0177) from E. faecalis V583 is involved in ABC transporter-mediated ribonucleoside uptake (30). Our data demonstrate for the first time that OG1RF_RS00630 participates in the development of OMC heteroresistance in E. faecalis.…”
Section: Discussionsupporting
confidence: 55%
“…Phylogenetic and homology analyses indicated that the efflux protein encoded by OG1RF_RS00630 is an ATPbinding cassette family protein expressed mainly in the cellular membrane. A previous study showed that the ortholog of OG1RF_RS00630 (EF0177) from E. faecalis V583 is involved in ABC transporter-mediated ribonucleoside uptake (30). Our data demonstrate for the first time that OG1RF_RS00630 participates in the development of OMC heteroresistance in E. faecalis.…”
Section: Discussionsupporting
confidence: 55%
“…The D39∆pnrA strain did not show significant changes in growth behavior compared to the wild-type in THY (data not shown) or in chemically defined medium RPMImodi. Likewise, no changes in growth behavior of homologous proteins in other bacteria were observed after the deletion of RnsB of S. mutans [17] and EF_0176 and EF_0177 of Enterococcus faecalis [32].…”
Section: Discussionmentioning
confidence: 93%
“…These are e.g. PnrA (TmpC) of T. pallidum [15], RnsB of S. mutans [17], EF_0176 and EF_0177 of Enterococcus faecalis [32], NupN of B. subtilis [5,33] and the substrate binding protein BpmA of L. lactis [16,34]. The transporters or their respective substrate binding proteins exhibit different substrate specificities.…”
Section: Introductionmentioning
confidence: 99%